МЕДИЦИНСКИЙ ТУРИЗМ: ИСТОРИЯ РАЗВИТИЯ, СУЩНОСТЬ И ОСНОВНЫЕ СОСТАВЛЯЮЩИЕ - Туракулов Маруф Хаккулович (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract. The purpose of this research was to study the history and development of medical tourism, given the definition of the term "medical tourism" at the present stage, its basic concepts. History of medical tourism has ancient roots, and each era of socio-economic development has its own peculiarities. First experience Given the definition of medical tourism, components, the impact of globalization processes on the formation of medical services.